Unit plans in technology education forms in lower secondary schools in the CARICOM : Part II - Gift, Edrick...[et al] ([CARICOM Secretariat] [Georgetown]GY, 2001)
Provides a foundation for teachers to develop lessons in technology. Focuses on four areas of technology viz. transportation, communication, production and biotechnology.